The relevance of whole or segmental body bioelectrical impedance phase angle and physical performance in adolescent athletes - Obayashi, H.; Ikuta, Y.; Fujishita, H.; Fukuhara, K.; Sakamitsu, T.; Ushio, K.; Kimura, H.; Adachi, N. (Physiological Measurement, 2021)
Objective. The physical condition of athletes can be assessed easily and quantitatively using objective indicators. Bioelectrical impedance measures the phase angle (PA), representing hydration and cell function, and is a potential clinical indicator of physical condition. This study aimed to investigate the association between PA and physical performance in adolescent athletes. Approach. Overall, 170 adolescent athletes underwent a sports medical check-up, including body composition measurements and physical performance tests. Whole-body and segmental PAs (arm and leg) were determined based on body composition values. Isometric grip power and knee isokinetic muscle strength were measured as parameters of muscle strength. Counter movement jump height and squat jump height were measured as jump parameters. Associations between PA and each muscle strength or jump parameters were analysed using Pearson product-moment correlation coefficient or Spearman's rank correlation coefficient. Main results. Whole-body and upper limb PAs were highly correlated with grip power (r = 0.70-0.80). Whole-body and lower limb PAs were correlated with knee isokinetic muscle strength (r = 0.43-0.59). Whole and all segmental PAs were correlated with counter movement jump height (r = 0.46-0.57) and squat jump height (r = 0.42-0.52). Significance. PA can be used to monitor physical condition and sports performance in adolescent athletes. Segmental PAs can help assess the condition of the corresponding body part.